Neuroeducational Strategies: A Way to Improve Attitude and Metacognition in University Students - González Cabrera, Silvia Yunuén (2023)
This article is a theoretical approach to neuroeducational strategies, as a possible path, to favor the attitude towards study and develop metacognitive skills in university students. Several studies have verified that a relevant variable to generate a positive attitude and develop metacognitive skills in university students is the teacher's teaching method. One of the sciences that favors educational processes is neuroeducation since despite being a relatively new science and several of its theories are still under investigation, it presents significant data on the study of the brain, its processes and offers relevant data for learning and the functions that support it. Upon concluding that neuroeducational strategies favor educational processes, we would have to do a second investigation on which are specifically the strategies that favor the attitude of students and develop their metacognitive skills.